RELATIONSHIP OF TRANSFORMATIONAL LEADERSHIP AN ORGANIZATIONAL ENVIRONMENT AT SECONDARY LEVEL - Dr.Fahd Naveed Kausar; Muhammad Kabir Khan; Hannan Akmal; Abdul Bari Qureshi (Policy Research Journal, 2024)
Transformational leadership fosters a positive organizational environment by promoting trust, innovation, and employee engagement through visionary and supportive leadership practices. This leadership style enhances collaboration, motivation, and adaptability, driving both individual growth and overall organizational success. The objective of the study was to find out the effect and relationship between transformational leadership (Inspirational Motivation, Idealized Influence, Intellectual Stimulation, and Individualized Consideration) and organizational environment at secondary level. The design of the study is correlational in nature. This study was quantitative research. The philosophical paradigm of quantitative research is positivism. The population was comprise all public and private (with more than 5 branches) secondary schools of Lahore district. The instrument of the study was questionnaires. The validity was found through expert’s opinions. Descriptive statistics and inferential statistics in Statistical Package for Social Sciences (SPSS), version 27 was used to analyze the data. Pearson r was used for 1st objective and regression analysis for 2nd objective. The findings of the study revealed that there was highly significant effect and relationship between transformational leadership (Inspirational Motivation, Idealized Influence, Intellectual Stimulation, and Individualized Consideration) and organizational environment at secondary level.